Role of Zn-Regulated Transporterand Iron (Fe)-Regulated Transporter-Like Protein (ZIP) Gene Family in Rice(Oryzasativa.L) in Foliar Application of Zinc as Bio Fortification Strategy to Enhance Grain Zinc Content - Deepak H. S, Shobha; S.M, Gopinath; A.G, Shankar; ., Rameshraddy. (International Journal of Engineering and Technology, 2018)
Cereal crops especially rice (Oryza sativa L.) play an important role in satisfying daily calorie intake in developing world, but they are inherently very low in zinc concentrations, more so when grown on zinc deficient soils. Biofortification is one among various immediate strategies for overcoming Zn deficiency in humans. Availability of soil applied zinc to the plant is limited by chemicalÂ and physical soil properties and hence foliar application of Zn is an effective strategy. Mobilization of foliar applied zinc and remobilization of plant accumulated zinc to grain is dependent on Zinc(Zn)-regulated transporter and iron(Fe)-regulated transporter-like protein(ZIP) gene family. Here we discuss the expression pattern of OsZIP1, OsZIP2, OsZIP3, OsZIP4, OsZIP5 and OsZIP7Â transportersin two different seed zinc genotypes(high grain zinc content types and low grainÂ zinc contentÂ types) at vegetative stage(65DAS) and at reproductive stage(50% panicle initiation)in stem, leaves and reproductive parts in response to Zn foliar applicationin the form of ZnSO4.7H2Oas an essential advance for understanding and manipulating the Zn absorption and translocation in rice. RT-PCR analysisÂ at 65DAS showed OsZIP1, OsZIP2, OsZIP7Â expressionÂ to be very minimal in leaves. OsZIP3Â andOsZIP4 expression was medium to highindicatingOsZIP3 and OsZIP4 to be actively involved in mobilization of foliar applied zinc from leaves.OsZIP1, OsZIP3 and OsZIP4 had higher activity at reproductive stage in leaf compared to vegetative stage suggesting their involvement in zinc remobilization/transport during reproductive stage.OsZIP4 and OsZIP7 hadhigher expression activity inÂ developing grains.There was no difference observed in expression levels of transporters among zinc types. There was large variability observed in zinc mobilization due to transporter function specificity and it is possibleÂ to enhance Zn content in grains under zinc sufficient conditions by direct foliar application at grain filling stage as transporters would facilitate this mobilization.Â